A Cross-Cultural Study of Neurophilosophy - Cheng, Kai-Yuan (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2011)
This paper will discuss the prospects of neuro-philosophy based on the works of Georg Northoff (2014a, b), a leading brain scientist and philosopher who has been conducting pioneering experiments on the neural-basis of self and consciousness. Engaged in vigorously philosophical thinking about the future of neurophilosophy, he claims that the empirical and the conceptual domains can and should be combined in a manner so as to significantly advance our understanding of the human mind. His conception of the brain as an organ that is intrinsically interconnected with a body and its environment sets him apart from some other influential neurophilosophers. Thus, the main purpose of this paper is to suggest that Northoff’s neurophilosophical project be situated and considered in a broader context, that is, in the context of Chinese Philosophy, such that insights and potentials on both sides may be better appreciated and more fully developed in future inquiries. To motivate my undertaking of a somewhat unusual and unexpected task like this, which is to connect two very different traditions—Eastern and Western—in a contemporary neural-inquiry of the human mind, some preparatory work is needed.